(untitled) (Heritage, 2025)
Christocentrism, as the most important characteristic of Christian culture, points to the annual liturgical cycle arranged according to events from Christ’s life, with the central place given to the birth and resurrection of Jesus Christ. The section of liturgics dealing with yearly feasts and their services involves the science of feasts, or heortology. In the liturgical cycle of the major Feasts of the Lord, such as the Nativity of Christ, the Circumcision of Christ, the Baptism of Christ (Epiphany), the Meeting of the Lord, Easter or Pascha (the feast of feasts, beyond all categories), the Ascension (the fortieth day after Easter), the Exaltation of the Holy Cross, the Transfiguration of the Lord, and the Entry of Jesus Christ into Jerusalem, the most significant events are the celebration of Christmas and Easter. This work uses aesthetic, philological, and theological approaches to highlight the significance of the festive genre in the works of one of the greatest writers of all time, Dostoevsky. Attention is focused on the phenomenon of festive texts and the celebration of Christmas and Easter. Through a theoretical approach, the meaning of this phenomenon will be established, a subject treated as an important aesthetic issue within Byzantine aesthetics, which encompasses the dimension of spiritual delight, culminating in spiritual catharsis. In Dostoevsky’s literary text, the Orthodox holiday is illuminated as a spiritual contact—a transcendent vision of the essential foundations of being, the hidden truths of the spirit, the laws of life in their fullness, and profound harmony with God, the experience of participating in eternity. Researching the festive text in literature involves a long and serious process of study.